Analisis Monitoring Kualitas Layanan Trafik Kamera CCTV padaJaringan Wifi - Fathoni, Fathoni; Rahayu, Rahayu (Universitas Bina Darma, 2015)
PT Bukit Asam is one of the major companies in Indonesia that have implemented the technology in the company by using IP-based CCTV cameras are connected to a network that is monitored in a single server. The purpose of the installation of cameras to reduce the risk of loss and asset security and performance of the network and its employees will increase. With the implementation of these technologies will require an IP camera as a liaison to the network. In the application of these technologies will be measured parameters quality of service (QoS) which includes throughput, packet loss and delay, so it appears the issues to be addressed in this study is a âAnalysis and Monitoring of Quality of Service Traffic CCTV Cameras In WiFi Networksâ.